2018
DOI: 10.3390/ijtpp3010004
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Experimental and Computational Methods for Modelling Multiple Row Effusion Cooling Performance

Abstract: Abstract:The continuing rise in turbine entry temperatures has necessitated the development of ever-more advanced cooling techniques. Effusion cooling is an example of such a system and is characterised by a high density of film cooling holes that operate at low blowing ratios, thereby achieving high overall cooling effectiveness. This paper presents both an experimental and computational investigation into the cooling performance of effusion systems. Two flat-plate geometries (with primary hole pitches of 3.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…Experiments by Muska et al [11] and more recently Murray et al [12] reaffirm the superposition method and its usefulness in predicting multi-row film cooling. The latter used a modified Goldstein Equation [13] (described later, but in the form of Equation ( 3)) to predict the film distribution of an individual hole and, when combined with Sellers' superposition, found the additive effect of multiple film hole rows.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Experiments by Muska et al [11] and more recently Murray et al [12] reaffirm the superposition method and its usefulness in predicting multi-row film cooling. The latter used a modified Goldstein Equation [13] (described later, but in the form of Equation ( 3)) to predict the film distribution of an individual hole and, when combined with Sellers' superposition, found the additive effect of multiple film hole rows.…”
Section: Introductionmentioning
confidence: 85%
“…The spanwise distance constant (c 1 ) and the spanwise shaping constant (c 2 ), which influence the spanwise film decay, are variables dependent on both the blowing ratio M and distance downstream of the film hole x. The values for these are based on experimental and correlation data, which can be found in [12,17].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated the film effectiveness of arrays of more tightly packed holes and porous media, albeit on flat plates. In a study by Murray et al [4], the effect of hole pitch of effusion cooled plates demonstrated that the for a given coolant output per unit area, reducing the pitch between coolant holes greatly improved the average film effectiveness of the studied plate. Reducing the pitch to hole diameter ratio from 5.75 to 3 more than doubled the effectiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the time, knowledge learnt from one setting could not be scaled for other operating situations or a simple addition of effects did not work. Murray et al [7] discussed effusion cooling as an example of stitching together multiple smaller film holes. It was characterized by a high density of smaller diameter film cooling holes operating at low blowing ratios with higher overall cooling effectiveness.…”
Section: Introductionmentioning
confidence: 99%